Numerical simulation of hydraulic fracture propagation under energy supplement conditions - Dong, Jingfeng; Qu, Hongyan; Zhang, Jingchun; Han, Feipeng; Zhou, Fujian; Shi, Peize; Shi, Jilong; Yu, Tianxi (Frontiers in Earth Science, 2023)
After the long-term production, due to the influence of low-pressure and low-stress fields in the near-well area, the reversion and propagation of new fractures after temporary plugging is short. It is difficult for the new fracture to extend to the remaining oil enrichment areas on both sides of the primary fractures, resulting in a low increase in the bandwidth of the fracture group after repeated fracturing, which affects the reservoir utilization. In the early stage of repeated fracturing, a large amount of pre-fracturing fluid is injected to supplement the energy of the fractures and rapidly increase the pore pressure in the local range, weakening rock strength and change the pore structure. In addition, the combination of energy replenishment and reservoir stimulation, coupled reconstruction of the seepage field and stress field, promotes the effective propagation of new fractures. However, in the process of increasing formation energy, the propagation law of hydraulic fractures and natural fractures is not clear. In this paper, the model of tight sandstone reservoir in the HQ block of Ordos Basin was established with the finite element software ABAQUS, based on the effective stress principle and the theoretical method of fluid-solid coupling numerical simulation. The propagation of a single hydraulic fracture and the interaction between hydraulic fracture and natural fracture under the condition of energy increase was investigated to better guide the field operation. The results show that for every 1 MPa pressure increase in a single hydraulic fracture, the fracture length increases by 0.62 m and the maximum fracture width decreases by 0.09 mm. When the formation energy increases by 6 MPa, the time for the hydraulic fracture to reach the intersection point with the natural fracture is shortened by 10 %, and the length of the natural fracture is 2.16 times compared with the case of 3 MPa energy increase.